Analysis Of Tobacco Marketing Channels In Boyolali Regency - Sulistyo Dewi, Alya; Setiyani, Rahmawati; Sepfrian, Bimoseno (LPPM Universitas Duta Bangsa Surakarta, 2024)
This study will analyze the tobacco marketing channel. It is hoped that there will be information as a reference in improving the flow of tobacco marketing so that it runs efficiently and marketing actors gain market benefits in accordance with their contributions. This study aims to analyze the tobacco marketing channel in Boyolali Regency. The data collection method in this study was conducted using interviews, documentation, and discussions. The number of samples can be calculated using the sample calculation method using the Lemeshow formula. The descriptive analysis method is aimed at solving current problems, not limited to collecting and compiling data but includes analyzing andinterpreting the meaning of the data. The results of the study explain that there are four tobacco marketing channels in Boyolali Regency; 1. Farmers-Cooperatives, 2. Farmers-Collectors-Wholesaler-Consumer, 3. Farmers-Wholesaler-Consumer, 4. Farmers-Consumer. It is expected that this study will provide a better understanding of how tobacco marketing channels operate in Boyolali Regency andprovide relevant suggestions to improve the efficiency of these marketing channels.